Pelaksanaan Pemblokiran Sertipikat Hak Atas Tanah Berdasarkan Permen ATR/Kepala BPN Nomor 13 Tahun 2017: Studi Kasus di Kantor Pertanahan Kabupaten Boyolali - Istiana, Istiana; Sutarni, Nanik; Pranawa, Burham (Fakultas Hukum, Universitas Boyolali, 2022)
Land registration is carried out to provide legal guarantees to holders of land rights. However, there are still many disputes that are the work of the government. This is because certificates as strong evidence have not been able to guarantee legal certainty for holders of property rights to the land, so that parties who feel entitled can block land rights at the Land Office. The implementation of the block is regulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 13 of 2017. This study aims to determine the process and procedure for blocking certificates at the Boyolali Regency Land Office and to find out the obstacles in the implementation of the blocking at the Boyolali Regency Land Office. Empirical juridical research method, by reviewing and explaining the study of research law in order to obtain objective research. Data was collected by interviewing the officers in the dispute section and officers in the land law relations section. Block registration is divided into two, namely blocks with cases attached and blocks without cases being attached. The fee that must be paid is Rp. 50,000.00 (fifty thousand rupiahs) in accordance with Government Regulation Number 128 of 2015, although later after the review process, the application for registration of blocking certificates is rejected. Not all requests for block registration were accepted even though they had paid the PNBP fee, this was because the reason for submitting the block was not in accordance with the provisions. The obstacle faced by the Boyolali Regency Land Office is that there are still many requirements that have not been fulfilled by the applicant in submitting a request for registration of blocking certificates, thus hampering the smooth implementation of recording blocking of certificates. In addition, the KKP Web application cannot be automatically deleted after 30 days of blocking registration without having to apply for the revocation of the certificate block. Pendaftaran tanah dilakukan untuk memberikan jaminan hukum kepada pemegang hak atas tanah. Akan tetapi masih banyak terjadi sengketa yang menjadi pekerjaan bagi pemerintah. Hal ini disebabkan sertipikat sebagai alat bukti yang kuat belum bisa menjamin kepastian hukum bagi pemegang hak milik atas tanah tersebut, sehingga pihak yang merasa berhak dapat melakukan blokir terhadap hak atas tanah pada Kantor Pertanahan. Pelaksanaan blokir diatur dalam Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 13 Tahun 2017. Penelitian ini bertujuan mengetahui proses serta prosedur pemblokiran sertipikat di Kantor Pertanahan Kabupaten Boyolali dan mengetahui hambatan dalam pelaksanaan pemblokiran di Kantor Pertanahan Kabupaten Boyolali. Metode penelitian yuridis empiris, dengan mengkaji dan menjelaskan kajian hukum penelitian agar mendapatkan penelitian yang objektif. Pengumpulan data dilakukan dengan wawancara kepada petugas seksi sengketa dan petugas di seksi hubungan hukum pertanahan. Pencatatan blokir dibagi dua, yaitu blokir dilampiri perkara dan blokir tanpa dilampiri perkara. Biaya yang wajib dibayar sebesar Rp. 50.000,00 (lima puluh ribu rupiah) sesuai Peraturan Pemerintah Nomor 128 Tahun 2015, walaupun nanti setelah proses pengkajian, permohonan pencatatan pemblokiran sertipikat ditolak. Permohonan pencatatan blokir tidak semua diterima meskipun sudah membayar biaya PNBP, hal tersebut dikarenakan alasan diajukannya blokir tidak sesuai dengan ketentuan. Hambatan yang dihadapi oleh Kantor Pertanahan Kabupaten Boyolali adalah masih banyak persyaratan yang belum terpenuhi oleh pemohon dalam mengajukan permohonan pencatatan pemblokiran sertipikat sehingga menghambat kelancaran dalam pelaksanaan pencatatan pemblokiran sertipikat.Selain itu, aplikasi KKP Web belum bisa secara otomatis terhapus dengan sendirinya setelah 30 hari pencatatan blokir tanpa harus mengajukan permohonan pencabutan blokir sertipikat